Optical incoherent direction finder as a part of a fault-tolerant complex for landing onto small bodies of the Solar System - Lobanov, A A; Alpatov, A N; Mozharov, G A; Torshina, I P; Troitsky, V I (Journal of physics. Conference series, 2020)
The subject of the study is the on-board guidance and navigation system for an autonomous landing of a space probe. The list of on-board equipment for safe landing of the spacecraft on the small bodies of the solar system (SBSS) is offered. The algorithm is proposed to combine all the on-board equipment into a single fault tolerance system. All the equipment is selected under the condition of the ability to identify failures at an early stage. The novelty of the method is in diversifying methods that are used in each stage of failure analysis. Such general method allows rejecting the results of some failure measurements from the further process thus preventing possible accident. The algorithm suggests two-stage control of the on-board systems that allows improving the fault tolerance. The first stage is based on the method of analysis of a number of double unequal measurements, but unlike the classical approach, it is assumed not to improve accuracy, but to search for errors. The second stage is based on the analysis of the parameters to control the internal equipment in order to predict failures.